Problem Based Learning, Discovery Learning, and Open Ended Models: An experiment On Mathematical Problem Solving Ability - Tanjung, Dian Fitria; Syahputra, Edi; Irvan, Irvan (Universitas Muhammadiyah Mataram, 2020)
This research is to look at the effect of problem-based learning, discovery learning, and open-ended models on the mathematical problem-solving abilities of students. The type of research is a quasi-experiment with a three treatment counterbalanced design research design. The instruments used: (1) students 'initial mathematical ability tests, (2) tests of students' mathematical problem-solving abilities with the Pythagorean Theorem material. Inferential data were performed using covariance analysis (ANACOVA). The samples of this study were 32 students each from three experimental classes selected by purposive sampling. The results are: (1) of the three learning models conducted using the model of problem-based learning, discovery learning, and open-ended had a positive effect on the ability to solve mathematical problems; (2) the ability to solve mathematical problems of students taught by problem-based learning models is better than the using discovery learning and open-ended models; and (3) there is an interaction between the initial ability of mathematics and learning models.